An interesting carcinoid tumor case followed up thirteen years - Selim GÜREL; Kadir DEMİR and Güngör BOZTAŞ and İzzet ROZANES and Sebahattin KAYMAKOĞLU and Sadakat ÖZDİL and Zeynel MUNGAN and Oktay YEĞİNSU and; la ÖKTEN (Turkish Journal of Gastroenterology, 2019)
-